RuP Nanoparticles Supported on N, O Codoped Porous Hollow Carbon for Efficient Hydrogen Oxidation Reaction. Issue 9 (6th February 2022) - Wang, Pengcheng; Wang, Changlai; Yang, Yang; Chen, Shi; Cheng, Zhiyu; Huang, Minxue; Tong, Huigang; Chen, Qianwang
Abstract: Highly active and low‐cost anodic hydrogen oxidation reaction (HOR) catalysts play a significant role in the large‐scale application of anion exchange membrane fuel cells (AEMFCs). Herein, a novel anodic HOR electrocatalyst with RuP nanoparticles loaded on N, O codoped porous hollow carbon (RuP/NOC) is prepared. The catalyst exhibits high catalytic activity toward HOR, achieving a kinetic mass activity of 3.25 mA µg –1 PGM at 50 mV, 13 times higher than that of Ru/NOC and even superior to that of Pt/C. Density functional theory (DFT) calculations demonstrate that the transfer of electrons from ruthenium to phosphorus shifts down the d‐band center of Ru, weakening the hydroxyl binding energy and decreasing the reaction energy barrier for HOR, thus enhancing the catalytic activity of Ru. Abstract : RuP nanoparticles loaded on N, O codoped porous hollow carbon (RuP/NOC) is designed as an active and robust hydrogen oxidation reaction (HOR) catalyst in alkaline medium. Density functional theory (DFT) calculations demonstrate that the transfer of electrons from ruthenium to phosphorus shifts down the d‐band center of Ru, weakening the hydroxyl binding energy, thus enhancing the catalytic activity for HOR.